MAKANAN ADAT DALAM ACARA BERINAI PADA RANGKAIAN UPACARAPERKAWINAN MELAYU DI DESA SEI GUNTUNG HILIR KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU RIAU - MUSPRIADI, MUSPRIADI; Chair, Ira Meirina; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research is motivatedtypical foodscarcityandlack ofknowledgeof the meaningoffoodin theMalaycustomaryceremonial processionBerinaiNight at villageSei Guntung Hilir Kecamatan Rengat Kabupaten Indragiri Hulu RiauThe purpose of this study is to describe the type of food and the meaning of food as well as customary hidang tools and presentation techniques used in ceremonial procession Berinai Night. The research is a qualitative study, the research object is customary foods served at the evening procession Berinai in Malay marriage ceremony. The instrument used in this study is the observation, interview and documentation. Data analysis using data reduction, data presentation, drawing conclusions and verification. The results showed that the type of food served at night Berinai consists of an assortment of dishes and pastries called